Identifying the features of ProVax and NoVax groups from social media conversations. (July 2021) - Furini, Marco
Abstract: Different studies state that doubts and fears posted on social media are making people hesitant towards vaccines and this hesitancy causes people to post doubts and fears. To break this vicious circle, we propose a method based on psycho-linguistics and time-domain analyses of social media conversations that talk about vaccines and vaccinations. The idea is to identify psycho-linguistics signals of distrust towards vaccines in order to help health authorities to restore the trust toward vaccines. The method allows the implementation of a well-known strategy used in marketing to restore the trust towards a brand when negative comments are posted on social media. The proposal has been evaluated using a two-year Facebook dataset composed of more than 170 thousand posts written by ProVax and NoVax people. The obtained results show that our method might be helpful to define a crisis communication plan to get people to trust vaccines, vaccinations and healthcare institutions again. Highlights: A communication strategy to fight vaccine social media misinformation was identified. A method to implement the communication strategy was proposed. Psycho-linguistic and time-domain analyses were used to implement the method. Evaluation was performed using more than 170, 000 Facebook messages. Users' interests and moods varied over time and were linked to real-world events.